THE INFLUENCE OF AUDITOR PROFESSIONAL ETHICS, AUDITOR COMPETENCE, AND COMPUTER-ASSISTED AUDIT TECHNIQUES ON AUDIT QUALITY AT PUBLIC ACCOUNTING FIRMS IN THE PEKANBARU REGION - Ananda, Sania; Fitriana, Nur; Rodiah, Siti (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study aims to examine the influence of auditor professional ethics, auditor competence, and computer-assisted audit techniques. In this study, the sample selection technique uses saturated sampling, which uses the entire population of this study as a sample, using primary data or direct questionnaire distribution to Pekanbaru Regional Public Accounting Firms. The analysis method used is multiple linear regression analysis using the SPSS version 26 program. The results of this study indicate that auditor professional ethics have an effect on audit quality, auditor competence has an effect on audit quality, and computer-assisted audit techniques also have an effect on audit quality.